Doxorubicin Dose Deintensification in Pediatric Osteosarcoma, Is Less Better? - Halalsheh, Hadeel; Abu-Hijlih, Ramiz; Ismael, Taleb; Shehadeh, Ahmad; Salaymeh, K. J.; Boheisi, Mohammad; Sultan, Iyad (South Asian Journal of Cancer, 2023)
Introduction We implemented new clinical practice guidelines (CPG) for patients with osteosarcoma starting in January 2009. These guidelines were based on standard European and American Osteosarcoma Study regimen, which includes six cycles of doxorubicin with a cumulative dose of 450 mg/m2. Aiming to reduce cardiac toxicity at our center, we opted to reduce the cumulative dose of doxorubicin to 375 mg/m2.Materials and Methods This is a retrospective cohort of osteosarcoma patients aged <18 years, treated at our center between 2009 and 2018. Patients were treated with unified CPG and were prospectively followed. Disease and treatment characteristics were depicted, and survival rates were calculated. When needed, comparison of survival of different groups were conducted using log-rank test.Results After a median follow-up of 43.3 months (range, 2–153 months), 79 patients were diagnosed with osteosarcoma and treated with dose-reduced doxorubicin. Median age at diagnosis was 12.8 years. At diagnosis, 58 patients (73%) had localized disease. The 5-year event-free survival (EFS) for the whole group was 50 ± 5.9%, and overall survival (OS) was 64 ± 5.7%. For patients with extremity nonmetastatic tumors (N = 56), 5-year EFS and OS were 60 ± 6.9% and 70 ± 6.8%, respectively, and for this group of patients, response to chemotherapy was associated with better EFS (p = 0.0048) and OS (p = 0.013). Only two patients suffered transient cardiac dysfunction, which was resolved after treatment.Conclusion Our findings suggest that deintensification of doxorubicin may provide adequate control for pediatric osteosarcoma. In the absence of large randomized clinical trials addressing this issue, developing countries with less resources to treat patients with heart failure may consider using the lower dose.
Keywords: osteosarcoma; doxorubicin; developing countries; cardiotoxicity